2019
DOI: 10.3390/app9122476
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Functionalized Carbon Structures with Optical Fiber Sensors in a Highly Alkaline Concrete Environment

Abstract: The paper presents an investigation into the durability of functionalized carbon structures (FCS) in a highly alkaline concrete environment. First, the suitability of optical fibers with different coatings-i.e., acrylate, polyimide, or carbon-for the FCS was investigated by subjecting fibers with different coatings to micro/macro bending and a 5% sodium hydroxide (NaOH) (pH 14) solution. Then, the complete FCS was also subjected to a 5% NaOH solution. Finally, the effects of spatial variation of the fiber embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The water in the pores of Portland cement is alkaline with a pH in the range between 12.5 and 13.5 [ 96 ]. Therefore, when functionalized TRCs are embedded into concrete, the highly alkaline environment might degrade the mechanical properties of both the optical glass fiber and the textile filaments as well as the bond between the two components, thus limiting the life-span and operation of the combined sensing and reinforcement structure.…”
Section: Functionalizing Textile-based Reinforcement Structure With Fossmentioning
confidence: 99%
See 3 more Smart Citations
“…The water in the pores of Portland cement is alkaline with a pH in the range between 12.5 and 13.5 [ 96 ]. Therefore, when functionalized TRCs are embedded into concrete, the highly alkaline environment might degrade the mechanical properties of both the optical glass fiber and the textile filaments as well as the bond between the two components, thus limiting the life-span and operation of the combined sensing and reinforcement structure.…”
Section: Functionalizing Textile-based Reinforcement Structure With Fossmentioning
confidence: 99%
“…Therefore, when functionalized TRCs are embedded into concrete, the highly alkaline environment might degrade the mechanical properties of both the optical glass fiber and the textile filaments as well as the bond between the two components, thus limiting the life-span and operation of the combined sensing and reinforcement structure. Therefore, the impact of highly alkaline concrete environments on the functionalized textile-based carbon reinforcement structure was investigated in [ 96 ]. In this study, the resistance of the functionalized textile-based reinforcement structure against the highly alkaline environments was explored depending on the coating of the optical glass fiber (acrylate, polyimide and carbon) and the tex-number of the textile filament (400, 800 and 1600 tex) of 300 mm long one-dimensional structures that have been fabricated according to the technique described in Section 4.1 [ 96 ].…”
Section: Functionalizing Textile-based Reinforcement Structure With Fossmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Bremer et al [1] reported an investigation on the feasibility of utilizing Mode Division Multiplexing (MDM) for simultaneous measurement of Surrounding Refractive Index (SRI) and temperature using a single sensor element based on an etched OM4 Graded Index Multi Mode Fiber (GI-MMF) with an integrated fiber Bragg Grating (BG). In another research article by Bremer et al [2], the durability of functionalized carbon structures (FCS) that are equipped with fiber optic sensors in a highly alkaline concrete environment are investigated. In their investigation, the suitability of optical fibers with different coatings as well as different integration techniques for the FCS were analyzed.…”
Section: Fiber Optical Sensingmentioning
confidence: 99%